Pentalogía de cantrell en el primer gemelo de un embarazo gemelar monocigótico: Presentación de un caso y revisión de la literatura (2011)
Introduction: Cantrell’s pentalogy (CP) consists of five anomalies: upper abdominal wall defects, lower sternal defects, anterior diaphragmatic defects, diaphragmatic pericardial defects and abnormalities of the heart. Around 250 cases have been reported; only 6 have involved twins and 4 of these have described discordance of such anomaly. Objective: presenting a case of twin pregnancy-associated CP and literature review regarding such association, emphasizing prenatal diagnosis and etiology.